Di-ureasil ormolytes doped with Mg2+ ions : part 1: morphological, thermal and electrochemical properties - Nunes, Sílvia (2005)
Poly(oxyethylene)(POE/siloxane-based materials incorporating magnesium triflate were prepared by the sol-gel process. The host Class II hybrid matrix (di-ureasil) employed was composed of a siliceous framework to which short POE chains were covalently bonded through urea linkages. Ormolytes with salt composition ranging from 500 to 1 were characterised. The nanohybrid with n = 20, thermally stable up to 360ºC, exhibited the highest ionic conductivity. The electrochemical stability of this material was found to span -3 to +2 volts.